Design of Syari'ah Resort in Barus, North Sumatera With a Religious Architecture Approach - Siregar, Moga Marina; Sitorus, Rudolf (Jurnal Koridor, 2023)
Islamic architecture is a form of structural art that takes inspiration from the Qur'an, the Sunnah of the Prophet, the Prophet's Family, Companions, Scholars, and Muslim scholars, as well as the physical and metaphysical features of buildings. The concept of Islamic Architecture can maintain harmony between nature and local culture, and sustainable designs must be used, protecting the environment from the planning stage onwards. Barus, which is the entrance to the Islamic Archipelago Civilization, has the potential to be developed into a favorite destination for pilgrims. The beautiful environment around Barus is an added value for this area because the beaches are still beautiful, and the people still adhere to their local wisdom. The object of study is to explore and implement religious-oriented design for resort hotel. The method we use is qualitative explorative research by reviewing some relevant-theory and synthesizing concept. The study formed the design statement: BarusÂ  as the "Zero Point of the Spread of Archipelago Islamic Civilization," which will attract domestic and international visitors, boost the local economy, and provide jobs for the local community. It is necessary to include a bit of Mandailing Batak culture as the majority ethnic group in Barus. The main objective of this sharia resort design is to create sharia-oriented atmosphere through the use of religious architecture and upholding positive human relations. Mosques, galleries, viewing towers, separate swimming pools for men and women, and other facilities are available at this resort, which will make visitors' vacations keep connecting to from Islamic concepts.